The Urgency of the State Budget Revision: Political and Legal Perspectives - Erawati, Erawati (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
This article aims to discuss the urgency of state budget revision and if the conditions, as stated in the MD3 Act are met, and the government takes steps not to propose an amended state budget with specific considerations, whether this government’s action is considered to violate the laws or regulations or not. This is a normative legal research that uses statute approach. The result of the study shows that the urgency of state budget revision is to ensure the soundness of the implementation of the current year's state budget by adjusting the amount of state revenue, state expenditure, budget deficits, and budget financing to more realistic levels that allow the achievement of specified development targets. In the light of the Presidential system in Indonesia, the government’s decision not to propose a revision of the state budget if the criteria to revise it, as stipulated in the State Finance Law and MD3 Law are fulfilled, theoretically is not a violation of the current laws and regulations. The choice to submit or not submit a revision of the state budget, after going through careful consideration by the government, is aimed at maintaining its credibility since the existence of a revision implies that the government is unable to undertake precise budget planning.